2016
DOI: 10.3389/fpubh.2016.00151
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Brain and Central Nervous System Tumor Incidence and Survival between the United States and Taiwan Based on Population-Based Registry

Abstract: PurposeReasons for worldwide variability in the burden of primary malignant brain and central nervous system (CNS) tumors remain unclear. This study compares the incidence and survival of malignant brain and CNS tumors by selected histologic types between the United States (US) and Taiwan.MethodsData from 2002 to 2010 were selected from two population-based cancer registries for primary malignant brain and CNS tumors: the Central Brain Tumor Registry of the United States and the Taiwan Cancer Registry. Two reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 31 publications
1
46
0
Order By: Relevance
“…In 2005, the World Health Organization reported that the global burden of neurological diseases exceeded that of cancer, HIV and heart disease 1 . The five primary categories of neuropathologies, ordered by frequency, are cerebrovascular diseases (stroke), neurodegenerative disorders (i.e., Parkinson's, Alzheimer's disease), neuroinfections (meningitis, viral infections), brain cancers (glioblastoma, astrocytoma and glioma) 2 ; and injuries of the central nervous system (CNS), such as traumatic brain injury 3 . Current examples of invasive drug delivery to the CNS include convection-enhanced delivery (CED, intracranial injection), intracerebral implants (Gliadel® BCNU chemotherapeutic wafers), as well as intraventricular, intrathecal and interstitial delivery (e.g., see needle track in Figure 1 A ).…”
Section: Introductionmentioning
confidence: 99%
“…In 2005, the World Health Organization reported that the global burden of neurological diseases exceeded that of cancer, HIV and heart disease 1 . The five primary categories of neuropathologies, ordered by frequency, are cerebrovascular diseases (stroke), neurodegenerative disorders (i.e., Parkinson's, Alzheimer's disease), neuroinfections (meningitis, viral infections), brain cancers (glioblastoma, astrocytoma and glioma) 2 ; and injuries of the central nervous system (CNS), such as traumatic brain injury 3 . Current examples of invasive drug delivery to the CNS include convection-enhanced delivery (CED, intracranial injection), intracerebral implants (Gliadel® BCNU chemotherapeutic wafers), as well as intraventricular, intrathecal and interstitial delivery (e.g., see needle track in Figure 1 A ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the use of aggressive treatment with surgery, radiation and chemotherapy, the 5-year overall survival rates for WHO grade III and IV gliomas are approximately only 25% and 5%, respectively. 1 Thus, there is an urgent need to improve the clinical management of this disease.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of CNS tumors is an important subject that could be affected of environmental and many other disparities which are inadequately understood [13]. Concerning to ethnic and racial consideration, brain tumors are less common in Asian Americans when compared with Whites in the USA and UK [1].…”
Section: Discussionmentioning
confidence: 99%
“…Dissimilarities in the brain and central nervous system (CNS) tumor incidence have been described among countries globally [1]. According to previously published report, the incidence of brain and CNS tumors of the Western world is higher than that of the Eastern world and higher in developed countries compared with less-developed countries [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation